The role of polysaccharides in immune regulation through gut microbiota: mechanisms and implications - Ting Zhao; Congyue Wang; Yuhan Liu; Bo Li; Mingjia Shao; Wuyang Zhao; Chuang Zhou (Frontiers in Immunology)
Polysaccharides, as complex carbohydrates, play a pivotal role in immune modulation and interactions with the gut microbiota. The diverse array of dietary polysaccharides influences gut microbial ecology, impacting immune responses, metabolism, and overall well-being. Despite their recognized benefits, there is limited understanding of the precise mechanisms by which polysaccharides modulate the immune system through the gut microbiota. A comprehensive search of Web of Science, PubMed, Google Scholar, and Embase up to May 2024 was conducted to identify relevant studies. This study employs a systematic approach to explore the interplay between polysaccharides and the gut microbiota, focusing on cytokine-mediated and short-chain fatty acid (SCFA)-mediated pathways. The findings underscore the significant role of polysaccharides in shaping the composition and function of the gut microbiota, thereby influencing immune regulation and metabolic processes. However, further research is necessary to elucidate the detailed molecular mechanisms and translate these findings into clinical applications.